2015
DOI: 10.1007/s13580-015-0135-9
|View full text |Cite
|
Sign up to set email alerts
|

Control of post-harvest anthracnose infection in guava (Psidium guajava) fruits with phosphites, calcium chloride, acetyl salicylic acid, hot water, and 1-MCP

Abstract: The control of anthracnose (Colletotrichum simmondsii) during the post-harvest stage in guava fruits (Psidium guajava L.) was performed by the application of phosphites [phosphite-K (40% P2O5 and 30% K2O) and phosphite-Ca (10.7% P2O5, 3.89% Ca, and 0.5% B)] including the Carbendazim as reference, calcium chloride (CaCl2), acetyl salicylic acid (ASA), hot water (HW), and 1-methylcyclopropene (1-MCP). These treatments were applied individually or in combination each other with two or three compounds. The evaluat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
17
0
4

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 27 publications
2
17
0
4
Order By: Relevance
“…'Isabel' grapes treated postharvest with CaCl 2 under ambient and modified atmospheres showed reduced fresh weight loss . However, the postharvest efficacy in maintaining fruit firmness seems to be higher when the use of CaCl 2 is combined with other bioregulators, such as 1-MCP, associated with hydrothermal treatment, as reported for guavas (CRUZ et al, 2015).…”
Section: Resultsmentioning
confidence: 84%
See 4 more Smart Citations
“…'Isabel' grapes treated postharvest with CaCl 2 under ambient and modified atmospheres showed reduced fresh weight loss . However, the postharvest efficacy in maintaining fruit firmness seems to be higher when the use of CaCl 2 is combined with other bioregulators, such as 1-MCP, associated with hydrothermal treatment, as reported for guavas (CRUZ et al, 2015).…”
Section: Resultsmentioning
confidence: 84%
“…The pre-harvesting use of CaCl 2 also led to the reduction of mass loss during storage of 'Venus' grapes (DANNER et al, 2009) and provided apples with greater firmness, especially when combined with postharvest hydrothermal treatment (SHARMA et al, 2013). In plums, treated with CaCl 2 associated with other bioactivators, Manganaris et al (2008) reported both the reduction in weight loss and retention in firmness during storage in plums, providing a higher resistance to fruits in postharvest.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations